2012
DOI: 10.1073/pnas.1216160109
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of contagious itch and why some people are more prone to it

Abstract: Watching someone scratch himself can induce feelings of itchiness in the perceiver. This provides a unique opportunity to characterize the neural basis of subjective experiences of itch, independent of changes in peripheral inputs. In this study, we first established that the social contagion of itch is essentially a normative response (experienced by most people), and that the degree of contagion is related to trait differences in neuroticism (i.e., the tendency to experience negative emotions), but not to em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
135
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(157 citation statements)
references
References 47 publications
11
135
3
4
Order By: Relevance
“…This partially agrees with a previous study where participants rated videos depicting scratching of the upper arm significantly itchier than the forearm and chest [3] . Of the 21 (64%) participants who produced spontaneous scratches in response to these videos, the majority were directed to the face and hair [7] , but there were no differences between males and females.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This partially agrees with a previous study where participants rated videos depicting scratching of the upper arm significantly itchier than the forearm and chest [3] . Of the 21 (64%) participants who produced spontaneous scratches in response to these videos, the majority were directed to the face and hair [7] , but there were no differences between males and females.…”
Section: Discussionsupporting
confidence: 82%
“…We also replicated our previous finding that self and other itch ratings correlated but there were no correlations between these and the scratch response. While it seems logical to assume that people scratch themselves when they feel "itchy" previous studies have identified only a weak correlation between itch perception and the scratch response [3] (see revised definition of itch proposed by Savin [11] in which the "threshold to scratch" is implemented), which suggests that the itch-scratch cycle is not absolute in that not all scratches are triggered by feelings of itch and not all feelings of itch result in scratching behavior. Although it seems subjective feeling states can be shared between the self and others, this occurs without obligatory motor stimulation [12,13] , reflecting the automatic and autonomous nature of scratching.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations